2019
DOI: 10.1021/acsomega.8b03581
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and “Green” Synthetic Route to Imidazo[1,2-a]pyridine by Cu(II)–Ascorbate-Catalyzed A3-Coupling in Aqueous Micellar Media

Abstract: An efficient and environmentally sustainable method for the synthesis of imidazo[1,2- a ]pyridine derivatives by domino A 3 -coupling reaction catalyzed by Cu(II)–ascorbate was developed in aqueous micellar media in the presence of sodium dodecyl sulfate (SDS). The catalyst, a dynamic combination of Cu(II)/Cu(I), was generated in situ in the reaction mixture by mixing CuSO 4 with sodium ascorbate and aided a facile 5- exo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
1
16
0
1
Order By: Relevance
“…According to the literature and our results, 11,14,22,25,31–35 a plausible reaction mechanism to account for the formation of imidazo[1,2- a ]pyridines is presented in Scheme 3 . The domino reaction begins with condensation between 2-aminopyridine (1a–b) and the pertinent aryl aldehyde derivatives (2a–e), followed by dehydration, resulting in the formation of a Schiff base (A).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…According to the literature and our results, 11,14,22,25,31–35 a plausible reaction mechanism to account for the formation of imidazo[1,2- a ]pyridines is presented in Scheme 3 . The domino reaction begins with condensation between 2-aminopyridine (1a–b) and the pertinent aryl aldehyde derivatives (2a–e), followed by dehydration, resulting in the formation of a Schiff base (A).…”
Section: Resultssupporting
confidence: 56%
“…A systemic perusal of the literature revealed that there are recent reports on several transition-metal-catalyzed techniques for the synthesis of imidazole-fused heterocyclic core nuclei. These catalytic strategies include the use of CuSO 4 ·5H 2 O, 11 MNP@BiimCu, 12 CuO/CuAl 2 O 4 , 13 Fe 3 O 4 @SiO 2 NPs, 14 CuI/ l -proline, 15 Cu–NPs 16 and nano-copper/nano-ZnAl 2 O 4 under an N 2 atmosphere, 17 PW-CIS500, 18 and CoFe 2 O 4 @CNT-Cu 19 towards the green synthesis of amalgamated heterocyclic moieties. However, these reported methods have some bottlenecks including the use of hazardous and expensive catalysts, extensive moisture-sensitive metallic reagents, harsh reaction conditions, prolonged reaction time, tedious work-up processes, use of volatile organic solvents and non-recyclable and large catalytic loading, leading to the generation of an enormous amount of waste.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazo[1,2- a ]pyridine derivatives were prepared by Cu( ii ) ascorbate catalyzed domino A 3 -coupling reaction in aqueous micellar media in the presence of anionic surfactant, sodium dodecyl sulfate (SDS) ( Scheme 30 ). 39 In this eco-friendly procedure, the catalyst used was a dynamic combination of Cu( ii )/Cu( i ), which was generated in the reaction mixture in situ by mixing CuSO 4 with sodium ascorbate. Imidazo[1,2- a ]pyridines were synthesized in good amount from 5- exo -dig cycloisomerization of alkynes with the condensation products of aldehydes and 2-aminopyridines.…”
Section: Synthesis Of Heterocyclesmentioning
confidence: 99%
“…通常, 通过一锅法多组分反应绿色高效地制备目标 分子是化学工作者的追求 [34] . 以 2-氨基吡啶、芳香醛和 末端炔烃为底物, 一锅法得到芳香醛中芳环位于咪唑环 的 2-位而非 3-位的产物 [35] . 例如, Rawat 课题组 [36] 以 CuIn 2 掺杂的石墨烯量子点为催化剂, 三组分经历了生 成五元环的 5-exo-dig 分子内环化反应, 得到了 2,3-二芳 基取代咪唑并[1,2-a]吡啶(Scheme 6).…”
Section: 以醛为原料unclassified